MUATAN ECO-DESIGN PADA LOMBA DESAIN FURNITUR JATENG TAHUN 2010 DAN 2011 - Sumarno - (Pendhapa, 2012)
Criteria on a design are reference or parameter of the success in a planning or designing. The criteria of the design competition of furniture products industry in Central Java consist of originality, ergonomic, environment friendly, market orientation, raw material efficiency, and the combination of alternative materials. The design criteria above, if they are grouped, will create rigid ecologic criteria domination, so that it can be categorized into an eco design planning and designing. This study tries to find out why the ecologic criteria are emphasized, and what kinds of design will become the winners and nominators. The point of view used in this study is ecologic and aesthetic study on the works of design competition. The sampling technique of this study is cluster sampling.The application of ecologic criteria in the design competition above is based on the global society’s demand on environment friendly products, and a consideration on the environment problems in Central Java. In determining the winners and the nominators, the juries more emphasize on the marketable aspects, whereas the environmental aspects have not got an appropriate portion. In doing the evaluation, the juries have done inconsistencies to the determined criteria. The design works of the finalists, in these design competition activities, have not fully applied the eco design principles. The application of environment friendly product design by the finalists generally is only on the finishing stage that is the using of finishing water base. Key words: eco design, design competition, and furniture industry